Pengaruh Karakter Disiplin terhadap Motivasi Belajar Siswa Kelas IV Pembelajaran Pendidikan Pancasila SDN 01 Moyoketen Tulungagung - Ragil Tania Anisah; Aldila Wanda Nugraha (Universitas Nusantara PGRI Kediri, 2024)
Having a disciplined character gives great satisfaction and appreciation to a person, because they know that their success is based on dedication and strong commitment to values. Motivation is defined as the driving force from within and outside an individual to carry out certain activities in order to achieve a goal. The location of the study was at SDN 1 Moyoketen School because it has implemented a disciplined character since early on. The purpose of this study was to determine the effect of disciplined character on the learning motivation of fourth grade students in Pancasila education learning at SDN 01 Moyoketen. This research method is quantitative research because the data obtained are in the form of numbers and analysis using statistics. The sample of this study was 41 respondents from all fourth grade populations using saturated sampling. In the calculation of the simple regression coefficient, the results showed that it was 0.008 and this value was smaller than 0.050 (0.008 <0.050), it can be concluded that the results of the analysis showed that the t count value (2,797)> t table (2.022) and the significance value was 0.008 <0.050. So it can be concluded that the character of discipline has a positive and significant effect on learning motivation. So this hypothesis is stated that Ho is rejected and Ha is accepted.